Metal Desorption from the Lichen Evernia prunastri (L.) Ach. Using Simulated Acid Rain pH Solutions - Ramić, Emina; Huremović, Jasna; Žero, Sabina (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2024)
In this study, the content of Cd, Cr, Cu, Fe, Mn, Ni, Pb, and Zn in washed and unwashed lichen Evernia prunastri (L.) Ach. was determined. Solutions similar to acid rain (H2SO4–HNO3–(NH4)2SO4–NH4NO3) with pH 2.02. 2.55, 3.61, 4.33, and 5.15 were used to investigate the desorption of metals from washed lichen Evernia prunastri. The metal analysis was conducted by flame atomic absorption spectrometry (FAAS). Content of Fe and Pb was higher in unwashed lichen, Mn and Ni were similar in washed and unwashed lichen, and Cr, Cu, Cd, and Zn were higher in the washed lichen sample. Using solution with pH 2.02, the percentage of desorbed Cu, Mn, Cd, and Zn was higher than 95%, while for Pb it was ~ 80%. Mn was desorbed in a mass percentage higher than 79%  in all simulated acid rain solutions, while the percentage of Cr desorption was less than 1%. Solutions with pH 3.61, 4.33, and 5.15 desorbed all metals except Mn in a percentage lower than 68%. The results indicate that the lichen Everina prunastri can become a secondary environment pollutant and that the mass percentage of desorbed metals depends on the strength of the bond between the metal and the components of the lichen tissue or cell wall, as well as on the pH value of the precipitation with which the lichen comes into contact.